THE INFLUENCE OF MATERNAL PERSONALITY TRAITS ON INFANT BEHAVIOURAL STYLE: IMPLICATIONS FOR EARLY INTERVENTION - Díaz Herrero, Ángela; Pérez López, Julio; Martínez Fuentes, María Teresa; Herrera Gutiérrez, Eva; Brito de la Nuez, Alfredo G. (Anales de Psicología / Annals of Psychology, 2000)
The aim of the present research was to investigate the relationships between maternal personality and their infants’ temperamental reactions when they are faced both to social and physical stimuli. For this purpose a sample of 38 infants and theirs mothers were studied. All newborns were full-term, without any pre and post-natal complication and belonging to a middle-class socioeconomic status. The mothers filled out the Cattell´s 16PF during the last trimester of pregnancy. Subsequently, at nine months of age, the infants were involved in different laboratory situations including persons and objects in order to exhibit their activity level, emotional tone and vocalizations. The results indicated that a predictive significant relationship exists between the maternal extroversion and emotional tone, activity level and vocalizations showed by theirs infants, when these are faced both to persons and objects.